Melampaui Subkultur/Post-Subkultur: Musisi sebagai Jalan Hidup Kaum Muda - Oki Rahadianto Sutopo; Gregorius Ragil Wibawanto; Agustinus Aryo Lukisworo (Universitas Gadjah Mada, 2020)
This study explores the struggle and its subjectivity among young people in Yogyakarta who choose being-musician as a way of life. Faced with limited job opportunity, they manage and keep alive their aspirations as mucisian in the local music scene. Their decisions to become musician embody a certain element of resistance against dominant view of work that encompasses the idea of a clear career projection. Even so, they do not always rely on the entrepreneurialism practice and do not neccesarily express class sentiment. Their diverse form of articulation is often constituted by construction of their subjectivity and lives trajectory. In this article, we use Hodkinson’s thought on ‘whole lives trajectories, Connel’s take on life in Global South and Beck’s theory on the redistribution of global risk to explore the subjectivity and plural voices of young musician in Yogyakarta. Based on the empirical data, we argue that throughout their lives trajectories, young musician intertwine with three social units that are unique to Global South context namely family, community, and wider social network either with subculture or post-subculture roots. In their lives trajectories—aside of those three social units—young musician are also faced with the redistribution of local and global risk.